Biometrical and behavioural associations with offering nuptial gifts by males in the spider Pisaura mirabilis. (July 2017) - Prokop, Pavol; Semelbauer, Marek
Abstract : Nuptial gifts are under strong selection in terms of female choice. It is hypothesized that nuptial gifts represent an honest signal resulting from the trade-off between self-maintenance and mating effort. Furthermore, nuptial gift size may correlate with certain personality traits, such as male fighting or hunting abilities. We investigated the nuptial gifts of a gift-giving spider, Pisaura mirabilis, consisting of both exogenous (prey) and endogenous (silk) components and their relationships to male biometry (the honest signalling hypothesis) and personality traits (the personality traits hypothesis). The gift's weight in the field was positively correlated with male size providing support for the honest signalling hypothesis. No differences in body condition and fluctuating asymmetry between males carrying and not carrying gifts in the field were found which does not support the honest signalling hypothesis. A substantial proportion of males offered worthless gifts that were smaller and lighter than genuine gifts. Reliable personality traits of males were not identified and no behavioural or survival differences between males carrying nuptial gifts, unwrapped prey and not carrying gifts in the field were observed. These results suggest that male size serves as an honest indicator of the exogenous component of the gift (i.e. the nuptial prey). Highlights: Pisaura mirablis males offer nuptial gifts to females. Gift weight positively correlated with male size in the field. Wrapped gifts were more frequently worthless than unwrapped prey. No personality traits were associated with offering a nuptial gift. Male size is suggested to signal the quality of the gift.